Evaluation of inflation forecasting models in Guatemala - Juan Carlos Casta\~neda-Fuentes; Héctor Augusto Valle-Samayoa; Juan Carlos Catalán-Herrera; Juan Carlos Arriaza-Herrera; Mariano José Gutiérrez-Morales; Carlos Eduardo Castillo-Maldonado; Douglas Napoleón Galindo-Gonzáles; Guisela Hurtarte-Aguilar; Edson Roger Ortiz-Cardona (Inter-American Development Bank (IDB), 2018)
Forecasting the inflation path is an important task for central banks in an inflation targeting regime. Therefore, central banks must continuously evaluate the forecasting accuracy of the models used to generate inflation forecasts. This paper evaluates the performance of most of the models that produce either unconditional or conditional inflation forecasts at Banco de Guatemala. The paper is divided in two main parts. The first part evaluates the forecasting accuracy and efficiency of the models that produce unconditional forecasts, applying different measures as normality test, root mean square error (RMSE), mean percentage errors (MPA), and tests as Diebold-Mariano, Pesaran-Timmerman, Giacomini-Rossi, as well as both weak and efficiency tests. The second part evaluates the conditional forecasting performance of the central bank's main macroeconomic models by generating sample forecasts in hindsight for different scenarios for exogenous and some endogenous variables. We find evidence supporting the claim that the time series models perform better in forecasting inflation for short time horizons while the structural macroeconomic models perform better in medium and long time horizons.
Keywords: C53; 330; Economic forecasting; Forecasting accuracy; Forecasting efficiency